Moral Philosophy and Politics (De Gruyter, 2014)
Moral Philosophy and Politics is an international, peer-reviewed journal for original philosophical articles on issues of public relevance. Of particular interest to the journal are the philosophical assessment of policy and its normative basis, analyses of the philosophical underpinnings or implications of political debate and reflection on the justice or injustice of the social and political structures which regulate human action.